Cladispa Baly: revision, biology and reassignment of the genus to the tribe Spilophorini (Coleoptera: Chrysomelidae: Cassidinae). (16th April 2014) - SEKERKA, LUKÁŠ; WINDSOR, DONALD; DURY, GUILLAUME
Abstract The genus, Cladispa Baly 1858, is transferred from the tribe Imatidiini (= Cephaloleiini Chapuis, 1875) to Spilophorini Chapuis, 1875 based on the review of type material, newly collected specimens and molecular phylogenetic analysis. The type species, C. quadrimaculata Baly, 1858, is redescribed, and two new species, C. amboroensissp.n. from Bolivia (Santa Cruz Department) and C. ecuadoricasp.n. from Ecuador (Pastaza Province), are described and figured. The morphology of C. amboroensissp.n. immature stages is broadly consistent with other Spilophorini. Field observations document that both C. quadrimaculata and C. amboroensissp.n. are trophic specialists on Orchideaceae. Keys to Cladispa species and Spilophorini genera are provided. Trophic associations of other Cassidinae and Orchideaceae are discussed. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:42A1ECF3‐2030‐4938‐8F3D‐FE7EC36F303A